2011
DOI: 10.1108/09684881111125041
|View full text |Cite
|
Sign up to set email alerts
|

Does internal quality management contribute to more control or to improvement of higher education?

Abstract: PurposeThe purpose of this paper is to explore faculty's perceptions of quality management activities (QMA) within their departments, attention being paid to relevant quality aspects and whether quality management contributes to control or improvement of higher education. Furthermore, it examines differences between departments and relationships between the different variables.Design/methodology/approachA questionnaire containing items with Likert‐type answer scales was distributed to faculty (n=266) of 18 dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
1
29
0
2
Order By: Relevance
“…The main findings about these processes on HEIs are presented below, organized into main topics that the literature review regarding perceptions about accreditation and quality management, has indicated as relevant (Busco, Dooner, & d'Alencon, 2018;Cardoso et al, 2013;Cardoso et al, 2015;IPSOS, 2010b;Kleijnen, Dolmans, Willems, & van Hout, 2011;Lemaitre, Maturana, Zenteno, & Alvarado, 2011;Scharager, 2017;Zapata & Torre, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The main findings about these processes on HEIs are presented below, organized into main topics that the literature review regarding perceptions about accreditation and quality management, has indicated as relevant (Busco, Dooner, & d'Alencon, 2018;Cardoso et al, 2013;Cardoso et al, 2015;IPSOS, 2010b;Kleijnen, Dolmans, Willems, & van Hout, 2011;Lemaitre, Maturana, Zenteno, & Alvarado, 2011;Scharager, 2017;Zapata & Torre, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cartwright (2007, p. 296) observa que los académicos con responsabilidades de gestión en los programas de calidad también son conscientes de que están tomando parte en un "juego" cuyas reglas se establecen fuera del ámbito académico. los planteamientos de Newton y Cartwright han hallado respuesta en un trabajo reciente de Kleijnen et al (2011), que llega a conclusiones similares a las de Elmuty et al (1996).…”
Section: El Significado De La Calidad De La Enseñanza Para Los Académunclassified
“…Para los partidarios de la gestión de la calidad en el sector universitario, el trabajo de Kleijnen et al (2011) ofrece una interpretación bastante amable. Sin embargo, los valores medios otorgados por los docentes a las afirmaciones sobre el impacto de la gestión de la calidad en la mejora de la enseñanza no son suficientemente altas -los propios autores los califican de "neutrales"-para concluir que existe unanimidad entre los docentes; al contrario, los resultados de Kleijnen et al son perfectamente compatibles con la existencia de posturas críticas entre los académicos.…”
Section: El Significado De La Calidad De La Enseñanza Para Los Académunclassified
“…Such outcomes are seen as capable of inducing improvement, especially in teaching and learning (Rosa et al, 2012, pp. 363-364), hence benefiting students, as well as academic work and decision-making processes (Huusko & Ursin, 2010;Kleijnen, Dolmans, Willems, & van Hout, 2011). Accreditation is also supported by those with managerial roles, who see it as providing the opportunity for institutions to reflect on their mission and purpose and 'to join an elite club' (Bell & Taylor, 2005, p. 248).…”
Section: Introductionmentioning
confidence: 96%